Cerebral Cortex Physiological Mapping in Health and Disease: From Animal Models to Clinical Applications - Mayevsky, Avraham (British Journal of Healthcare and Medical Research, 2025)
Normal brain cortical activity is an integration of many biochemical and physiological processes including hemodynamic, metabolic, ionic homeostasis and electrical activities. In order to evaluate the functional state of the brain, it is necessary to monitor in real time as many parameters as possible. We developed the concept of “Cerebral Cortex Physiological Mapping” that describes the interrelations between the various parameters measured by the multiparametric monitoring system (MPA). We used these systems in experimental animal models as well as in neurosurgical patients. Our approach aims are to monitor, in real-time, a small volume of the cerebral cortex containing all the tissue elements that are parts of a typical functioning brain tissue. We are interested in the microenvironment of the brain containing neurons, glia, synapses and the microcirculatory elements (small arterioles and capillaries). The various parameters and the technology developed are presented in the attached figure. During the development process we pursued the goal of being minimally invasive in terms of the penetration to the cortical tissue itself. It was obvious that the various probes could not monitor the same volume of tissue due to the size of each probe used. Therefore, we attempted to minimize the diameter of the various probes located in the MPA that had a 5-6 mm contact area with the cerebral cortex. In most of the perturbations used, such as global ischemia, anoxia, hypoxia or hemorrhage, most of the areas in the cortex will respond in the same way. We used these monitoring system in experimental animal models exposed to pathophysiological conditions. Changes in oxygen supply were induced by hypoxia, ischemia or hypeoxia. The level of brain activity was changed by epilepsy or cortical spreading depression. The key monitored parameter, in all monitoring systems, was the oxidation-reduction state of NADH, representing the mitochondrial function in vivo and in real-time. This parameter provided information on oxygen supply as well as oxygen balance in the brain. In the current review, the various systems developed since 1972 will be presented including a typical record of the results obtained.